R&D, organization structure, and the development of corporate technological knowledge - Argyres, Nicholas; Silverman, Brian S. (Strategic Management Journal, 2004)
Abstract We explore the link between a firm's organization of research—specifically, its choice to operate a centralized or decentralized R&D structure—and the type of innovation it produces. We propose that by reducing the internal transaction costs associated with R&D coordination across units, centralized R&D will generate innovations that have a larger and broader impact on subsequent technological evolution than will decentralized research. We also propose that, by facilitating more distant (‘capabilities‐broadening’) search, centralized R&D will generate innovations that draw on a wider range of technologies. Our empirical results provide support for our predictions concerning impact, and mixed results for our predictions concerning breadth of search. We also find that control over research budgets complements direct authority relations in contributing to innovative impact. We propose several extensions of this research. Copyright © 2004 John Wiley & Sons, Ltd.